Mapping the Key Concepts in Gender Studies and Creating a Cartography of Their Balkan Specificities - Arsenijević, Damir, Bogojević, Maja, Demiragić, Ajla, Petrović, Jelena, Potkonjak, Sanja (Array, 2007)
This article offers a narrative which maps out of a wide range of specificities of gender studies in the Balkans, more precisely in Bosnia and Herzegovina, Croatia, Montenegro and Slovenia. The choice of the countries analysed here was guided by us based on our individual involvement in furthering gender/women’ s studies in higher education research and teaching as well as on our experiences of being travelling scholars and working closely with each other, both formally and informally. Firmly embedded in our concrete practices and mutual collaboration, our aim is to inform and tease out, question and assess, locate and chart. We have chosen to tell a story about ourselves in such a way so as to draw on those similarities and differences that will continue a novel and productive interaction between theory and practice, activism and the academia.